The Contents of the Social Science Textbook used in Assam’s Upper Primary Education Curriculum: An Emphasis on Encouraging Civic Engagement and Social Accountability - Nizara Devi Adhikari; Prof. (Dr.) Minati Choudhury (Revista Electronica de Veterinaria, 2025)
In the present study, the social science textbook used in Assam’s Upper Primary curriculum which normally covers Classes VI through VIII is examined. Key elements of geography, history, political science (civics), and economics are included into the textbook, which was created in accordance with the National Curriculum Framework (NCF) and under the direction of the Assam State Textbook Production and Publication Corporation Ltd. Students’ critical thinking, civic engagement, and socio-cultural understanding will all be fostered by the content’s emphasis on raising awareness of both local and national settings. Modules that showcase Assam’s rich historical past, cultural variety, ethnic populations, and environmental aspects lay a heavy emphasis on regional identity. Instilling democratic values and knowledge of modern socio-political institutions are other goals of the textbook. Disparities in inclusive representation and educational approaches are revealed by critical analysis, nevertheless, especially with relation to gender perspectives, indigenous histories, and participatory learning techniques. An in-depth analysis of how the textbook affects students’ understanding of society and their place in it can be started with this abstract, which also advocates for a more inclusive, participatory, and student-centered curriculum framework.